Effect of Chitosan Supplementation to drinking water in productive performance, physiological and micro flora traits of broiler - Ahmed T. Taha; Ahmed A. Allaw (Kufa Journal for Veterinary Medical Sciences, 2016)
This study carried out in the farms of animal production department /College of Agriculture /University of Tikrit during the period from 15/2/2014 to 22/3/2014. It aims to investigate effect of adding chitosan to the drinking water on the productive performance and some physiological characteristics and intestinal micro flora of broiler. A total of 150 unsexed  broiler chinks at 21 day of old divided to five treatments by three replicates (10 per each ) , the first treatment  without any adding ( control treatment ), in the 2ed ,3ed , 4th and 5th treatment was adding chitosan to drinking water by concentration (100,150,200 and 250 mg/l) respectively